Knowledge, attitude, and practices of renal diets among hemodialysis patients - Saumiya Kanagarajah; Supriya Velraja; Hemamalini Janardhanan Arambakkam (Biomedical and Biotechnology Research Journal, 2022)
Background: Malnutrition and mineral disparities has become increasingly common in patients with the end-stage renal disease treated with hemodialysis (HD). Lack of nutritional knowledge is one of the most significant reasons for nutritional problems leading to improper practice and causing several complications. The objectives of the study were to asses the nutrition knowledge, attitude, and practice of HD patients regarding renal diet, to counsel the patients on HD dietary guidelines and to determine the association of factors such as income and education level on nutrition management of HD Patients. To assess the nutrition knowledge, attitude, and practice of HD patients regarding renal diet. To counsel the patients on HD dietary guidelines. To determine the association of factors such as income and education level on nutrition management of HD patients. Methods: A total of 120 patients undergoing HD were assessed for the level of nutrition knowledge, attitude, and practice, regarding HD dietary guidelines, using a validated questionnaire. Results: About 60.3% of HD patients had excellent knowledge, 60% had excellent attitude, and 40% had excellent practices. There is a significant positive correlation between knowledge and attitude, as well as knowledge and practice (r < 0.01) of the patients undergoing HD regarding renal diet. There is also a significant association between the knowledge, attitude, and practice scores with the selected demographical variables (education level and income) of patients at the significance level of P < 0.001. Conclusion: Although majority of the patients have excellent knowledge, attitude, and practice, a notable number of patients are unaware about their dietary guidelines and do not adhere to the dietary regime that needs to be followed. Diet counseling by a renal dietitian using a nutrition education module can effectively upgrade the nutrition knowledge, attitude, and practice of HD dietary guidelines by the patients.